Effects of Atrazine exposure on human bone marrow-derived mesenchymal stromal cells assessed by combinatorial assay matrix - Uwazie, Crystal C.; Pirlot, Bonnie M.; Faircloth, Tyler U.; Patel, Mihir; Parr, Rhett N.; Zastre, Halie M.; Hematti, Peiman; Moll, Guido; Rajan, Devi; Chinnadurai, Raghavan (Frontiers in Immunology, 2023)
Leading regulatory agencies, such as the US Food and Drug Administration (FDA) and the European Medicines Agencies (EMA) now endorse the use of the Combinatorial Assay Matrix Approach / Technology in both toxicity screening and manufacturing of advanced cellular therapeutics. We here employed this novel approach in a representative manner to profile the response of human primary Mesenchymal Stromal/Stem Cells (MSCs), which are of key relevance in human physiology and well-being, to the common environmental xenobiotic Atrazine.